High-strength light release film and preparation method thereof
By adopting a three-layer structure release film design, combining porous foam PS and amphiphilic micron network particles, the problem of insufficient performance of the existing release film is solved, and the balance between high strength and light weight is achieved, which meets the semiconductor packaging and optics Strict functional requirements in the fields of devices and other fields.
Patent Information
- Application Number
- CN202411159041.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2024-12-31
AI Technical Summary
The existing release films have insufficient performance in applications with high strength and light weight requirements, which are difficult to meet the strict functional requirements in the fields of semiconductor packaging, optical devices and micro-nano-scale devices.
A release film design with a three-layer structure, in which the intermediate layer is a porous foam PS, supercritical foaming is superficially foamed by adding cellulose nanocrystals to form a closed cell structure, and amphiphilic micron network particles are added to the upper and lower layers to improve density and mechanics performance.
The balance between high strength and light weight is achieved, the mechanical properties and adhesion properties of the release film are improved, and the application needs of high strength and light weight are met.
Smart Images

Figure BDA0005005911470000091 
Figure BDA0005005911470000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of release films, and in particular to a high-strength and lightweight release film and a preparation method thereof. Background Art
[0002] Release film, also known as isolation film, peeling film, separation film, etc., is a functional film material widely used in many fields. Its main function is to be non-sticky or slightly sticky when in contact with specific materials under limited conditions, so as to achieve functions such as isolation, filling, protection and easy peeling. There are various types of release films, which can be distinguished according to substrate, release force, color and surface treatment. With the development of science and technology, release films have broad application prospects in various fields such as semiconductor packaging, optical devices, energy storage and micro-nano scale devices. The requirements for it are becoming more and more stringent, or the requirements for its functionality are becoming higher and higher. In addition to its basic release function, its precise adhesion performance, excellent protection performance, excellent mechanical strength and light weight are key technical features. Therefore, by modifying the release film and designing the structure, it is also of great market value to prepare a release film with high strength, light weight and good release effect. Summary of the invention
[0003] Technical problem to be solved: In view of the above technical problems, the purpose of the present invention is to provide a high-strength and lightweight release film and a preparation method thereof, which adopts a three-layer structure, with the middle layer being a porous foam PS, and the upper and lower layers being release layers with dense surfaces. The middle foam layer can greatly reduce the weight of the release film, and the upper and lower layers are release layers with dense surfaces. This microstructure combining internal porosity and surface density can maintain the strength of the release film.
[0004] Technical solution: A high-strength and lightweight release film, the release film is three-layered, the middle layer is porous foam PS, and the upper and lower layers are release layers with dense surfaces; The cells of the porous foam PS are a closed-cell structure. Furthermore, the preparation method of the porous foam PS is: Step 1: After drying, add cellulose nanocrystals to PS and obtain PS composite material after banburying. The banburying temperature is 190°C, the speed is 50r / min, and the banburying time is 10min; Step 2: The PS composite material is melted and hot-pressed using a flat vulcanizer at a temperature of 190°C, a pressure of 30 MPa, and a hot-pressing time of 10 min. After the hot-pressing is completed, it is cooled to room temperature to obtain a film with a thickness of 5 μm; Step 3: Place the film in an autoclave, introduce CO2, set the supercritical pressure to 25MPa, set the temperature to 70-100°C, and perform swelling for 3-5h for supercritical foaming. After the supercritical foaming is completed, quickly release the CO2 in the autoclave and transfer it to cold water to fix the pore structure, thereby obtaining a porous foam PS. Furthermore, the mass content of the cellulose nanocrystals in the PS composite material is 1.0-4.0%. The method for preparing the above-mentioned high-strength and lightweight release film comprises the following steps, measured in parts by weight: S1: Take 3-6 parts of amphiphilic micron network particles, disperse them in 25 parts of formamide solution, add 5 parts of 1 mg / ml PVA aqueous solution, stir evenly, add 1-2 parts of glutaraldehyde, and stir for 30 minutes; S2: Add 60 parts of water, stir evenly and cast onto one side of the porous foam PS, and vacuum dry at 40°C for 8 hours; S3: After taking out, cast it onto the other side of the porous foam PS, and vacuum dry it at 40°C for 24 hours. Furthermore, the amphiphilic micron network particles have hydrophilic and hydrophobic properties, a particle size of 0.1-5 μm, a three-dimensional network structure, and nanopores on the surface. Furthermore, the preparation method of the amphiphilic micron network particles is as follows: S11: Dissolve 0.5-1.5 parts of agarose in 100 parts of deionized water, add 50-60 parts of Al2O3 powder, 5 parts of TiO2 powder, 2 parts of MgO powder and 5 parts of polyvinyl alcohol in sequence, stir evenly, and ball mill wet mix for 2 hours; S12: vacuum degassing the slurry, heating it to 80° C. in a constant temperature water bath, pouring the slurry into a mold, cooling it, and drying it naturally at room temperature; S13: taking out and placing in a pressureless sintering furnace for sintering at a temperature of 1400-1500°C for 1 hour at a heating rate of 5°C / min, and cooling with the furnace; S14: broken into micron network particles; S15: Take 120 parts of isopropanol, 0.24 parts of tetramethylammonium hydroxide and 2.5 parts of water, mix them evenly at 60° C., add 15 parts of a mixture of phenyltriethoxysilane and γ-aminopropyltriethoxysilane, and stir evenly; S16: immersing in micron network particles and reacting for 20 h; S17: Add 3 parts of 30% H2O2, react at 45°C for 12-15 hours, adjust the pH to neutral with NaOH solution, filter, and wash to obtain amphiphilic micron network particles. Furthermore, the mass ratio of the phenyltriethoxysilane to the γ-aminopropyltriethoxysilane is (1-3):(3-1). Beneficial effects: 1. The present invention adopts a three-layer structure, the middle layer is porous foam PS, the upper and lower layers are release layers with dense surfaces, the middle foam layer can greatly reduce the weight of the release film, and the upper and lower layers are release layers with dense surfaces. This microstructure combining internal porosity and surface density can maintain the strength of the release film. 2. In the preparation of porous foam PS, the present invention uses cellulose nanocrystals as nucleating agents. Cellulose nanocrystals have a significant heterogeneous nucleation effect on PS foaming. After addition, the pore size becomes smaller, more uniform, and has good formability and relatively better mechanical properties. At the same time, closed cells are produced, which is more convenient for the later cast release layer. 3. The present invention uses agarose as a raw material to prepare three-dimensional network particles. When the agarose is cooled after being heated to high temperature, hydrogen bonds will occur within the molecules and between the molecules, and a double helix structure will be formed by hydrogen bonds generated between sugar groups, and the double helix structure will gradually aggregate to eventually form a three-dimensional network structure. After sintering, dense micron network particles are obtained. After amphiphilic modification, the micron network particles have both hydrophilicity and hydrophobicity. The hydrophilicity can make it firmly bonded to the substrate PVA, and the hydrophobicity can make it enriched on the surface of the PVA film, thereby reducing the surface tension of the PVA film and improving the release effect. At the same time, the surface of the micron network particles also has nanopores, which can form a micro-nano structure on the surface of the release film, further improving the release effect. 4. In addition, the amphiphilic micron network particles can also improve the density of the PVA film and serve as a skeleton support material to improve the mechanical properties of the release film. 5. The present invention uses sulfonate groups as hydrophilic units and benzene rings as hydrophobic units to prepare amphiphilic micron network particles. The sulfonate groups are obtained by in-situ oxidation of thiol-containing particles obtained by hydrolysis co-condensation reaction to generate sulfonate groups. DETAILED DESCRIPTION The present invention proposes a high-strength and lightweight release film and a preparation method thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention will be further described in detail with reference to the embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Example 1 The preparation method of porous foam PS is: Step 1: After drying PS, 1.0 wt.% cellulose nanocrystals were added, and the PS composite material was obtained after banburying at a banburying temperature of 190°C, a rotation speed of 50 r / min, and a banburying time of 10 min; Step 2: The PS composite material is melted and hot-pressed using a flat vulcanizer at a temperature of 190°C, a pressure of 30 MPa, and a hot-pressing time of 10 min. After the hot-pressing is completed, it is cooled to room temperature to obtain a film with a thickness of 5 μm; Step 3: Place the film in an autoclave, introduce CO2, set the supercritical pressure to 25 MPa, the temperature to 70°C, and the swelling time to 5 hours for supercritical foaming. After the supercritical foaming is completed, quickly release the CO2 in the autoclave and transfer it to cold water to fix the pore structure, thereby obtaining a porous foam PS. Example 2 The preparation method of porous foam PS is: Step 1: After drying PS, 3.0 wt.% cellulose nanocrystals were added, and the PS composite material was obtained after banburying at a banburying temperature of 190°C, a rotation speed of 50 r / min, and a banburying time of 10 min; Step 2: The PS composite material is melted and hot-pressed using a flat vulcanizer at a temperature of 190°C, a pressure of 30 MPa, and a hot-pressing time of 10 min. After the hot-pressing is completed, it is cooled to room temperature to obtain a film with a thickness of 5 μm; Step 3: Place the film in an autoclave, introduce CO2, set the supercritical pressure to 25 MPa, the temperature to 90°C, and the swelling time to 4 hours for supercritical foaming. After the supercritical foaming is completed, quickly release the CO2 in the autoclave and transfer it to cold water to fix the pore structure, thereby obtaining a porous foam PS. Example 3 The preparation method of porous foam PS is: Step 1: After drying PS, 4.0 wt.% cellulose nanocrystals were added, and the PS composite material was obtained after banburying at a banburying temperature of 190°C, a rotation speed of 50 r / min, and a banburying time of 10 min; Step 2: The PS composite material is melted and hot-pressed using a flat vulcanizer at a temperature of 190°C, a pressure of 30 MPa, and a hot-pressing time of 10 min. After the hot-pressing is completed, it is cooled to room temperature to obtain a film with a thickness of 5 μm; Step 3: Place the film in an autoclave, introduce CO2, set the supercritical pressure to 25 MPa, the temperature to 100°C, and the swelling time to 3 hours for supercritical foaming. After the supercritical foaming is completed, quickly release the CO2 in the autoclave and transfer it to cold water to fix the pore structure, thereby obtaining a porous foam PS. Comparative Example 1 The difference between this comparative example and Example 2 is that no cellulose nanocrystals are added, specifically as follows: The preparation method of porous foam PS is: Step 1: Take PS and dry it, and then obtain PS material after banburying. The banburying temperature is 190°C, the speed is 50r / min, and the banburying time is 10min; Step 2: The PS composite material is melted and hot-pressed using a flat vulcanizer at a temperature of 190°C, a pressure of 30 MPa, and a hot-pressing time of 10 min. After the hot-pressing is completed, it is cooled to room temperature to obtain a film with a thickness of 5 μm; Step 3: Place the film in an autoclave, introduce CO2, set the supercritical pressure to 25 MPa, the temperature to 90°C, and the swelling time to 4 hours for supercritical foaming. After the supercritical foaming is completed, quickly release the CO2 in the autoclave and transfer it to cold water to fix the pore structure, thereby obtaining a porous foam PS. Determination of average cell size: The average cell size was calculated by counting the diameters of 150 cells; Determination of cell density: unit volume (cm 3 ) The number of cells contained in the Determination of expansion ratio: The density of the sample before foaming is divided by the density after foaming to obtain: Table 1 Average cell size (μm) <![CDATA[Cell density (number of cells / cm 3 )]]> Expansion ratio Example 1 78.5 <![CDATA[6.2×10 10 ]]> 11.6 Example 2 50.4 <![CDATA[3.1×10 11 ]]> 10.4 Example 3 39.6 <![CDATA[8.7×10 11 ]]> 9.1 Comparative Example 1 100.5 <![CDATA[9.5×10 6 ]]> 11.5 Based on various performance indicators of the foaming material, Example 2 was selected for subsequent experiments. Example 4 The preparation method of amphiphilic micron network particles is as follows: S11: Dissolve 0.5 parts of agarose in 100 parts of deionized water, add 55 parts of Al2O3 powder, 5 parts of TiO2 powder, 2 parts of MgO powder and 5 parts of polyvinyl alcohol in sequence, stir evenly, and ball mill wet mix for 2 hours; S12: vacuum degassing the slurry, heating it to 80° C. in a constant temperature water bath, pouring the slurry into a mold, cooling it, and drying it naturally at room temperature; S13: taking out and placing in a pressureless sintering furnace for sintering at a temperature of 1450°C for 1 hour at a heating rate of 5°C / min, and cooling with the furnace; S14: crushed into micron network particles with a particle size of 0.1-5 μm; S15: Take 120 parts of isopropanol, 0.24 parts of tetramethylammonium hydroxide and 2.5 parts of water, mix them evenly at 60° C., add 15 parts of a mixture of phenyltriethoxysilane and γ-aminopropyltriethoxysilane, and stir evenly; the mass ratio of phenyltriethoxysilane to γ-aminopropyltriethoxysilane is 2:1; S16: immersing in micron network particles and reacting for 20 h; S17: Add 3 parts of 30% H2O2, react at 45°C for 14 hours, adjust the pH to neutral with NaOH solution, filter, and wash to obtain amphiphilic micron network particles. Example 5 The preparation method of amphiphilic micron network particles is as follows: S11: Dissolve 1.0 part of agarose in 100 parts of deionized water, add 55 parts of Al2O3 powder, 5 parts of TiO2 powder, 2 parts of MgO powder and 5 parts of polyvinyl alcohol in sequence, stir evenly, and ball mill wet mix for 2 hours; S12: vacuum degassing the slurry, heating it to 80° C. in a constant temperature water bath, pouring the slurry into a mold, cooling it, and drying it naturally at room temperature; S13: taking out and placing in a pressureless sintering furnace for sintering at a temperature of 1450°C for 1 hour at a heating rate of 5°C / min, and cooling with the furnace; S14: crushed into micron network particles with a particle size of 0.1-5 μm; S15: Take 120 parts of isopropanol, 0.24 parts of tetramethylammonium hydroxide and 2.5 parts of water, mix them evenly at 60° C., add 15 parts of a mixture of phenyltriethoxysilane and γ-aminopropyltriethoxysilane, and stir evenly; the mass ratio of phenyltriethoxysilane to γ-aminopropyltriethoxysilane is 2:1; S16: immersing in micron network particles and reacting for 20 h; S17: Add 3 parts of 30% H2O2, react at 45°C for 14 hours, adjust the pH to neutral with NaOH solution, filter, and wash to obtain amphiphilic micron network particles. Example 6 The preparation method of amphiphilic micron network particles is as follows: S11: Dissolve 1.5 parts of agarose in 100 parts of deionized water, add 55 parts of Al2O3 powder, 5 parts of TiO2 powder, 2 parts of MgO powder and 5 parts of polyvinyl alcohol in sequence, stir evenly, and ball mill wet mix for 2 hours; S12: vacuum degassing the slurry, heating it to 80° C. in a constant temperature water bath, pouring the slurry into a mold, cooling it, and drying it naturally at room temperature; S13: taking out and placing in a pressureless sintering furnace for sintering at a temperature of 1450°C for 1 hour at a heating rate of 5°C / min, and cooling with the furnace; S14: crushed into micron network particles with a particle size of 0.1-5 μm; S15: Take 120 parts of isopropanol, 0.24 parts of tetramethylammonium hydroxide and 2.5 parts of water, mix them evenly at 60° C., add 15 parts of a mixture of phenyltriethoxysilane and γ-aminopropyltriethoxysilane, and stir evenly; the mass ratio of phenyltriethoxysilane to γ-aminopropyltriethoxysilane is 2:1; S16: immersing in micron network particles and reacting for 20 h; S17: Add 3 parts of 30% H2O2, react at 45°C for 14 hours, adjust the pH to neutral with NaOH solution, filter, and wash to obtain amphiphilic micron network particles. Example 7 The preparation method of amphiphilic micron network particles is as follows: S11: Dissolve 1.0 part of agarose in 100 parts of deionized water, add 50 parts of Al2O3 powder, 5 parts of TiO2 powder, 2 parts of MgO powder and 5 parts of polyvinyl alcohol in sequence, stir evenly, and ball mill wet mix for 2 hours; S12: vacuum degassing the slurry, heating it to 80° C. in a constant temperature water bath, pouring the slurry into a mold, cooling it, and drying it naturally at room temperature; S13: taking out and placing in a pressureless sintering furnace for sintering at a temperature of 1400°C for 1 hour at a heating rate of 5°C / min, and cooling with the furnace; S14: crushed into micron network particles with a particle size of 0.1-5 μm; S15: Take 120 parts of isopropanol, 0.24 parts of tetramethylammonium hydroxide and 2.5 parts of water, mix them evenly at 60° C., add 15 parts of a mixture of phenyltriethoxysilane and γ-aminopropyltriethoxysilane, and stir evenly; the mass ratio of phenyltriethoxysilane to γ-aminopropyltriethoxysilane is 1:1; S16: immersing in micron network particles and reacting for 20 h; S17: Add 3 parts of 30% H2O2, react at 45°C for 14 hours, adjust the pH to neutral with NaOH solution, filter, and wash to obtain amphiphilic micron network particles. Example 8 The preparation method of amphiphilic micron network particles is as follows: S11: Dissolve 1.0 part of agarose in 100 parts of deionized water, add 50 parts of Al2O3 powder, 5 parts of TiO2 powder, 2 parts of MgO powder and 5 parts of polyvinyl alcohol in sequence, stir evenly, and ball mill wet mix for 2 hours; S12: vacuum degassing the slurry, heating it to 80° C. in a constant temperature water bath, pouring the slurry into a mold, cooling it, and drying it naturally at room temperature; S13: taking out and placing in a pressureless sintering furnace for sintering at a temperature of 1400°C for 1 hour at a heating rate of 5°C / min, and cooling with the furnace; S14: crushed into micron network particles with a particle size of 0.1-5 μm; S15: Take 120 parts of isopropanol, 0.24 parts of tetramethylammonium hydroxide and 2.5 parts of water, mix them evenly at 60° C., add 15 parts of a mixture of phenyltriethoxysilane and γ-aminopropyltriethoxysilane, and stir evenly; the mass ratio of phenyltriethoxysilane to γ-aminopropyltriethoxysilane is 1:3; S16: immersing in micron network particles and reacting for 20 h; S17: Add 3 parts of 30% H2O2, react at 45°C for 14 hours, adjust the pH to neutral with NaOH solution, filter, and wash to obtain amphiphilic micron network particles. Example 9 The preparation method of amphiphilic micron network particles is as follows: S11: Dissolve 1.0 part of agarose in 100 parts of deionized water, add 60 parts of Al2O3 powder, 5 parts of TiO2 powder, 2 parts of MgO powder and 5 parts of polyvinyl alcohol in sequence, stir evenly, and ball mill wet mix for 2 hours; S12: vacuum degassing the slurry, heating it to 80° C. in a constant temperature water bath, pouring the slurry into a mold, cooling it, and drying it naturally at room temperature; S13: taking out and placing in a pressureless sintering furnace for sintering at a temperature of 1500°C for 1 hour at a heating rate of 5°C / min, and cooling with the furnace; S14: crushed into micron network particles with a particle size of 0.1-5 μm; S15: Take 120 parts of isopropanol, 0.24 parts of tetramethylammonium hydroxide and 2.5 parts of water, mix them evenly at 60° C., add 15 parts of a mixture of phenyltriethoxysilane and γ-aminopropyltriethoxysilane, and stir evenly; the mass ratio of phenyltriethoxysilane to γ-aminopropyltriethoxysilane is 2:1; S16: immersing in micron network particles and reacting for 20 h; S17: Add 3 parts of 30% H2O2, react at 45°C for 12 hours, adjust the pH to neutral with NaOH solution, filter, and wash to obtain amphiphilic micron network particles. Example 10 The preparation method of amphiphilic micron network particles is as follows: S11: Dissolve 1.0 part of agarose in 100 parts of deionized water, add 60 parts of Al2O3 powder, 5 parts of TiO2 powder, 2 parts of MgO powder and 5 parts of polyvinyl alcohol in sequence, stir evenly, and ball mill wet mix for 2 hours; S12: vacuum degassing the slurry, heating it to 80° C. in a constant temperature water bath, pouring the slurry into a mold, cooling it, and drying it naturally at room temperature; S13: taking out and placing in a pressureless sintering furnace for sintering at a temperature of 1500°C for 1 hour at a heating rate of 5°C / min, and cooling with the furnace; S14: crushed into micron network particles with a particle size of 0.1-5 μm; S15: Take 120 parts of isopropanol, 0.24 parts of tetramethylammonium hydroxide and 2.5 parts of water, mix them evenly at 60° C., add 15 parts of a mixture of phenyltriethoxysilane and γ-aminopropyltriethoxysilane, and stir evenly; the mass ratio of phenyltriethoxysilane to γ-aminopropyltriethoxysilane is 2:1; S16: immersing in micron network particles and reacting for 20 h; S17: Add 3 parts of 30% H2O2, react at 45°C for 15 hours, adjust the pH to neutral with NaOH solution, filter, and wash to obtain amphiphilic micron network particles. Comparative Example 2 The difference between this comparative example and Example 5 is that carrageenan is used instead of agarose, as follows: The preparation method of amphiphilic micron network particles is as follows: S11: Dissolve 1.0 part of carrageenan in 100 parts of deionized water, add 55 parts of Al2O3 powder, 5 parts of TiO2 powder, 2 parts of MgO powder and 5 parts of polyvinyl alcohol in sequence, stir evenly, and ball mill wet mix for 2 hours; S12: vacuum degassing the slurry, heating it to 80° C. in a constant temperature water bath, pouring the slurry into a mold, cooling it, and drying it naturally at room temperature; S13: taking out and placing in a pressureless sintering furnace for sintering at a temperature of 1450°C for 1 hour at a heating rate of 5°C / min, and cooling with the furnace; S14: crushed into micron network particles with a particle size of 0.1-5 μm; S15: Take 120 parts of isopropanol, 0.24 parts of tetramethylammonium hydroxide and 2.5 parts of water, mix them evenly at 60° C., add 15 parts of a mixture of phenyltriethoxysilane and γ-aminopropyltriethoxysilane, and stir evenly; the mass ratio of phenyltriethoxysilane to γ-aminopropyltriethoxysilane is 2:1; S16: immersing in micron network particles and reacting for 20 h; S17: Add 3 parts of 30% H2O2, react at 45°C for 14 hours, adjust the pH to neutral with NaOH solution, filter, and wash to obtain amphiphilic micron network particles. Comparative Example 3 The difference between this comparative example and Example 5 is that phenyltriethoxysilane is not added, and γ-aminopropyltriethoxysilane is used instead, as follows: The preparation method of amphiphilic micron network particles is as follows: S11: Dissolve 1.0 part of agarose in 100 parts of deionized water, add 55 parts of Al2O3 powder, 5 parts of TiO2 powder, 2 parts of MgO powder and 5 parts of polyvinyl alcohol in sequence, stir evenly, and ball mill wet mix for 2 hours; S12: vacuum degassing the slurry, heating it to 80° C. in a constant temperature water bath, pouring the slurry into a mold, cooling it, and drying it naturally at room temperature; S13: taking out and placing in a pressureless sintering furnace for sintering at a temperature of 1450°C for 1 hour at a heating rate of 5°C / min, and cooling with the furnace; S14: crushed into micron network particles with a particle size of 0.1-5 μm; S15: Take 120 parts of isopropanol, 0.24 parts of tetramethylammonium hydroxide and 2.5 parts of water, mix them evenly at 60° C., and then add 15 parts of γ-aminopropyltriethoxysilane; S16: immersing in micron network particles and reacting for 20 h; S17: Add 3 parts of 30% H2O2, react at 45°C for 14 hours, adjust the pH to neutral with NaOH solution, filter, and wash to obtain amphiphilic micron network particles. Comparative Example 4 The difference between this comparative example and Example 5 is that the reaction time in S17 is 5 h, as follows: The preparation method of amphiphilic micron network particles is as follows: S11: Dissolve 1.0 part of agarose in 100 parts of deionized water, add 55 parts of Al2O3 powder, 5 parts of TiO2 powder, 2 parts of MgO powder and 5 parts of polyvinyl alcohol in sequence, stir evenly, and ball mill wet mix for 2 hours; S12: vacuum degassing the slurry, heating it to 80° C. in a constant temperature water bath, pouring the slurry into a mold, cooling it, and drying it naturally at room temperature; S13: taking out and placing in a pressureless sintering furnace for sintering at a temperature of 1450°C for 1 hour at a heating rate of 5°C / min, and cooling with the furnace; S14: crushed into micron network particles with a particle size of 0.1-5 μm; S15: Take 120 parts of isopropanol, 0.24 parts of tetramethylammonium hydroxide and 2.5 parts of water, mix them evenly at 60° C., add 15 parts of a mixture of phenyltriethoxysilane and γ-aminopropyltriethoxysilane, and stir evenly; the mass ratio of phenyltriethoxysilane to γ-aminopropyltriethoxysilane is 2:1; S16: immersing in micron network particles and reacting for 20 h; S17: Add 3 parts of 30% H2O2, react at 45°C for 14 hours, adjust the pH to neutral with NaOH solution, filter, and wash to obtain amphiphilic micron network particles. The surface tension of the amphiphilic micro-network particles was measured at a concentration of 0.6%. Table 2 Based on various properties of the amphiphilic micron network particles, the amphiphilic micron network particles prepared in Example 5 were selected for subsequent experiments. Embodiment 11 A method for preparing a high-strength and lightweight release film comprises the following steps, measured in parts by weight: S1: Take 3 parts of amphiphilic micron network particles, disperse them in 25 parts of formamide solution, add 5 parts of 1 mg / ml PVA aqueous solution, stir evenly, add 1.5 parts of glutaraldehyde, and stir for 30 minutes; S2: Add 60 parts of water, stir evenly and cast onto one side of the porous foam PS, and vacuum dry at 40°C for 8 hours; S3: After taking out, cast onto the other side of the porous foam PS, and vacuum dried at 40°C for 24 hours to obtain a high-strength and lightweight release film with a thickness of 100 μm. Example 12 A method for preparing a high-strength and lightweight release film comprises the following steps, measured in parts by weight: S1: Take 4 parts of amphiphilic micron network particles, disperse them in 25 parts of formamide solution, add 5 parts of 1 mg / ml PVA aqueous solution, stir evenly, add 1.5 parts of glutaraldehyde, and stir for 30 minutes; S2: Add 60 parts of water, stir evenly and cast onto one side of the porous foam PS, and vacuum dry at 40°C for 8 hours; S3: After taking out, cast onto the other side of the porous foam PS, and vacuum dried at 40°C for 24 hours to obtain a high-strength and lightweight release film with a thickness of 100 μm. Example 13 The preparation method of the high-strength and light-weight release film comprises the following steps, measured in parts by weight: S1: Take 5 parts of amphiphilic micron network particles, disperse them in 25 parts of formamide solution, add 5 parts of 1 mg / ml PVA aqueous solution, stir evenly, add 1.5 parts of glutaraldehyde, and stir for 30 minutes; S2: Add 60 parts of water, stir evenly and cast onto one side of the porous foam PS, and vacuum dry at 40°C for 8 hours; S3: After taking out, cast onto the other side of the porous foam PS, and vacuum dried at 40°C for 24 hours to obtain a high-strength and lightweight release film with a thickness of 100 μm. Embodiment 14 A method for preparing a high-strength and lightweight release film comprises the following steps, measured in parts by weight: S1: Take 6 parts of amphiphilic micron network particles, disperse them in 25 parts of formamide solution, add 5 parts of 1 mg / ml PVA aqueous solution, stir evenly, add 1.5 parts of glutaraldehyde, and stir for 30 minutes; S2: Add 60 parts of water, stir evenly and cast onto one side of the porous foam PS, and vacuum dry at 40°C for 8 hours; S3: After taking out, cast onto the other side of the porous foam PS, and vacuum dried at 40°C for 24 hours to obtain a high-strength and lightweight release film with a thickness of 100 μm. Embodiment 15 A method for preparing a high-strength and lightweight release film comprises the following steps, measured in parts by weight: S1: Take 5 parts of amphiphilic micron network particles, disperse them in 25 parts of formamide solution, add 5 parts of 1 mg / ml PVA aqueous solution, stir evenly, add 1 part of glutaraldehyde, and stir for 30 minutes; S2: Add 60 parts of water, stir evenly and cast onto one side of the porous foam PS, and vacuum dry at 40°C for 8 hours; S3: After taking out, cast onto the other side of the porous foam PS, and vacuum dried at 40°C for 24 hours to obtain a high-strength and lightweight release film with a thickness of 100 μm. Example 16 A method for preparing a high-strength and lightweight release film comprises the following steps, measured in parts by weight: S1: Take 5 parts of amphiphilic micron network particles, disperse them in 25 parts of formamide solution, add 5 parts of 1 mg / ml PVA aqueous solution, stir evenly, add 2 parts of glutaraldehyde, and stir for 30 minutes; S2: Add 60 parts of water, stir evenly and cast onto one side of the porous foam PS, and vacuum dry at 40°C for 8 hours; S3: After taking out, cast onto the other side of the porous foam PS, and vacuum dried at 40°C for 24 hours to obtain a high-strength and lightweight release film with a thickness of 100 μm. Comparative Example 5 The difference between this embodiment and embodiment 13 is that no amphiphilic micron network particles are added, specifically: The preparation method of the release film comprises the following steps, measured in parts by weight: S1: Take 5 parts of 1 mg / ml PVA aqueous solution, add 1.5 parts of glutaraldehyde, and stir for 30 minutes; S2: Add 60 parts of water, stir evenly and cast onto one side of the porous foam PS, and vacuum dry at 40°C for 8 hours; S3: After taking out, cast onto the other side of the porous foam PS, and vacuum dried at 40° C. for 24 hours to obtain a release film with a thickness of 100 μm. Comparative Example 6 The difference between this embodiment and comparative example 13 is that porous foam PS is not used, specifically: The preparation method of the release film comprises the following steps, measured in parts by weight: S1: Take 5 parts of amphiphilic micron network particles, disperse them in 25 parts of formamide solution, add 5 parts of 1 mg / ml PVA aqueous solution, stir evenly, add 1.5 parts of glutaraldehyde, and stir for 30 minutes; S2: Add 60 parts of water, stir evenly and then cast into a mold, and vacuum dry at 40°C to obtain a release film with a thickness of 100 μm. The release film prepared in the above embodiment was cut into 1 cm×4 cm strips, and its mechanical properties were measured using a universal stretching machine with a loading speed of 2 mm / min and a stretching speed of 5 mm / min. The release force of the release film was tested by ASTM D3330 / D3330M-04 (2018). The results are shown in Table 3: Table 3 <![CDATA[Density (g / cm 3 )]]> Flexural strength(MPa) Release force (cN / 2.5cm) Embodiment 11 0.34 83.6 17.6 Example 12 0.35 84.1 17.4 Example 13 0.35 85.5 17.1 Embodiment 14 0.36 85.7 17.0 Embodiment 15 0.35 85.1 17.1 Example 16 0.35 85.6 17.2 Comparative Example 5 0.35 41.0 38.6 Comparative Example 6 1.45 90.8 17.1
Claims
1. A high-strength and lightweight release film, characterized in that: The release film is three-layered, the middle layer is porous foam PS, and the upper and lower layers are release layers with dense surfaces; The cells of the porous foam PS are a closed-cell structure.
2. A high-strength and lightweight release film according to claim 1, characterized in that: The preparation method of the porous foam PS is: Step 1: After drying, add cellulose nanocrystals to PS and obtain PS composite material after banburying. The banburying temperature is 190°C, the speed is 50r / min, and the banburying time is 10min; Step 2: The PS composite material is melted and hot-pressed using a flat vulcanizer at a temperature of 190°C, a pressure of 30 MPa, and a hot-pressing time of 10 min. After the hot-pressing is completed, it is cooled to room temperature to obtain a film with a thickness of 5 μm; Step 3: Place the film in an autoclave, introduce CO2, set the supercritical pressure to 25MPa, set the temperature to 70-100°C, and perform swelling for 3-5h for supercritical foaming. After the supercritical foaming is completed, quickly release the CO2 in the autoclave and transfer it to cold water to fix the pore structure, thereby obtaining a porous foam PS.
3. A high-strength and light-weight release film according to claim 2, characterized in that: The mass content of the cellulose nanocrystals in the PS composite material is 1.0-4.0%.
4. The method for preparing a high-strength and light-weight release film according to any one of claims 1 to 3, characterized in that: The method comprises the following steps, in parts by weight: S1: Take 3-6 parts of amphiphilic micron network particles, disperse them in 25 parts of formamide solution, add 5 parts of 1 mg / ml PVA aqueous solution, stir evenly, add 1-2 parts of glutaraldehyde, and stir for 30 minutes; S2: Add 60 parts of water, stir evenly and cast onto one side of the porous foam PS, and vacuum dry at 40°C for 8h; S3: After taking out, cast it onto the other side of the porous foam PS, and vacuum dry it at 40°C for 24 hours.
5. The method for preparing a high-strength and light-weight release film according to claim 4, characterized in that: The amphiphilic micron network particles have hydrophilic and hydrophobic properties, a particle size of 0.1-5 μm, a three-dimensional network structure, and nanopores on the surface.
6. The method for preparing a high-strength and light-weight release film according to claim 4, characterized in that: The preparation method of the amphiphilic micron network particles is as follows: S11: Dissolve 0.5-1.5 parts of agarose in 100 parts of deionized water, add 50-60 parts of Al2O3 powder, 5 parts of TiO2 powder, 2 parts of MgO powder and 5 parts of polyvinyl alcohol in sequence, stir evenly, and ball mill wet mix for 2 hours; S12: vacuum degassing the slurry, heating it to 80° C. in a constant temperature water bath, pouring the slurry into a mold, cooling it, and drying it naturally at room temperature; S13: taking out and placing in a pressureless sintering furnace for sintering at a temperature of 1400-1500°C for 1 hour at a heating rate of 5°C / min, and cooling with the furnace; S14: broken into micron network particles; S15: Take 120 parts of isopropanol, 0.24 parts of tetramethylammonium hydroxide and 2.5 parts of water, mix them evenly at 60° C., add 15 parts of a mixture of phenyltriethoxysilane and γ-aminopropyltriethoxysilane, and stir evenly; S16: immersing in micron network particles and reacting for 20 h; S17: Add 3 parts of 30% H2O2, react at 45°C for 12-15 hours, adjust the pH to neutral with NaOH solution, filter, and wash to obtain amphiphilic micron network particles.
7. The method for preparing a high-strength and light-weight release film according to claim 6, characterized in that: The mass ratio of the phenyltriethoxysilane to the γ-aminopropyltriethoxysilane is (1-3):(3-1).